Compositional, micromorphological and geotechnical characterization of Holocene Tiber floodplain deposits (Rome, Italy) and sequence stratigraphic implications. Issue 4 (3rd February 2022) - Tentori, Daniel; Mancini, Marco; Milli, Salvatore; Stigliano, Francesco; Tancredi, Simone; Moscatelli, Massimiliano
Abstract: This study reports a high‐resolution micromorphological characterization of floodplain deposits to investigate the relationships among compositional, textural and geotechnical data, and integrate soil micromorphology with sequence stratigraphy. Compositional and textural characterization of facies associations and soil features are calibrated against geotechnical parameters. The latter, obtained from cone penetration and pocket penetrometer tests from a borehole advanced 60 m into the Tiber channel belt and floodplain, show that depositional features and post‐depositional modifications are intrinsically associated with cone penetration test parameters: cone resistance; sleeve friction; and friction ratio. Petrographic and micromorphological features document pedogenetic modifications across stratigraphic markers evidenced by faunal and plant activity, accumulation of peat, and typified by precipitation of heavy metals, iron oxides and secondary carbonates. All of these features developed in correspondence with alluvial flooding surfaces that are correlated with non‐marine and marine flooding surfaces recognized in the transgressive and highstand coastal and lagoonal deposits of the Tiber Depositional Sequence. These observations may serve as a model to reconstruct the sequence‐stratigraphic evolution of ancient relict soils. Nevertheless, additional criteria (for example, their stratigraphic position and correlative surfaces) are necessary to adequately interpret the genesis of such low‐rank stratigraphic surfaces. This work demonstrates that a combination between sedimentological and stratigraphic observations and soil micromorphology can be critical to supplement field observations and determine the relative effect of pedogenic and depositional processes on the organization, composition and texture, and geotechnical properties of floodplain in urban areas.